The Role Of Assembly Taklim Nagari Desa Baru In Increasing Community Religiusity Kecamatan Ranah Batahan - Edy Juarminson; Aguswan Aguswan; Romi Yilhas (Ruhama : Islamic Education Journal, 2023)
Majelis taklim is a form of informal religious education that develops in society. This study aims to reveal the role of majelis taklim Nagari Desa Baru kecamatan  Ranah Batahan Pasaman Barat in increasing knowledge and understanding. the practice and religiosity of the people towards Islamic teachings. The results of the study show that the majelis taklim plays an active role in increasing people's religiosity towards Islam. The role of the majelis taklim is realized in the form of: majelis taklim as a place to study religion; majelis taklim as a place to strengthen ukhuwah Islamiyah; majelis taklim as reinforcement of aqidah and morals; the majelis taklim as a means of tahsin reading the Koran and the majelis taklim as a place for correcting the implementation of worship. The implications of this study are expected for the supervisors, administrators, members of the majelis taklim in particular and the general public in order to maintain and enhance the role of the majelis taklim in the community as a means of increasing people's religiosity towards Islamic teachings.